Proceedings of the 33rd Annual ACM Conference Extended Abstracts on Human Factors in Computing Systems 2015
DOI: 10.1145/2702613.2732513
|View full text |Cite
|
Sign up to set email alerts
|

Behind The Scenes at HCI's Turn to the Arts

Abstract: Since 2000, Human Computer Interaction (HCI) has seen a turn to the artistic, looking at more provocative, cultural and social experiences. In doing so HCI is increasingly collaborating with artists who engage with real world data. Much of this work focuses on engaging the public in the spectacle of interactive experiences. In contrast, this paper takes a look behind the scenes by studying a collaboration between artists, climate scientists and researchers as they designed a participatory sensing system to int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Besides its artistic merit, the study revealed that confrontation with an ethically challenging technology helped people recognize the need to understand the usage and sharing of personal data by companies. Yet, while the value of artistic representations has proven to benefit audience engagement [33,47], we believe it is equally important to stimulate discussion about ethics by provoking response through design-oriented objects that reflect real-life application scenarios and that exemplify prob-lematic aspects of an emerging technology. Enabling the public to walk up to a realistic demonstrator that blends in with its environment, to interact with it, and to experience individual implications seems a relevant approach to collect ecologically valid feedback on ethical use of emerging technologies.…”
Section: Designing For Speculation On Ethical Implicationsmentioning
confidence: 99%
“…Besides its artistic merit, the study revealed that confrontation with an ethically challenging technology helped people recognize the need to understand the usage and sharing of personal data by companies. Yet, while the value of artistic representations has proven to benefit audience engagement [33,47], we believe it is equally important to stimulate discussion about ethics by provoking response through design-oriented objects that reflect real-life application scenarios and that exemplify prob-lematic aspects of an emerging technology. Enabling the public to walk up to a realistic demonstrator that blends in with its environment, to interact with it, and to experience individual implications seems a relevant approach to collect ecologically valid feedback on ethical use of emerging technologies.…”
Section: Designing For Speculation On Ethical Implicationsmentioning
confidence: 99%
“…We also direct the reader to the substantial body of work led by Steve Benford's team at the Mixed Reality Laboratory. Through longstanding collaboration with mixed-reality artist group Blast Theory, Benford et al have extensively used forms of interactive moving images in combination with interactive/immersive elements to explore social interactions between performers, participants and audiences in public space [1,4,8,9,10]. Wiliamson and Williamson conducted an exploration of evaluation methods for publicly situated research in the wild [14], focussing specifically on how evaluator intervention influences the nature of research.…”
Section: Aims and Scope Of The Workhopmentioning
confidence: 99%
“…In many areas of ACM SIGCHI, large numbers of researchers use arts-based methods to inform their practice [5,8]. These performance applications regularly involve moving images, such as live projections and immersive performance spaces, and foster interactivity through performative elements.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional cultural environments, such as museums, have not been exempted from this trend. [Jacobs et al, 2015] [ Vancat and Riha, 2012] For instance Gonz ález, Organero and Kloos [Gonz ález et al, 2008] 0:4 Nilsson et al attempted to find the best way of utilizing ubiquitous computing to develop an infrastructure for innovative learning spaces. They concluded that, much due to their versatility, mobile phones will in the near future be able to support all the different types of processes needed in learning scenarios.…”
Section: Related Workmentioning
confidence: 99%